Pengaruh Motivasi kerja terhadap Kinerja Pegawai pada Dinas Tenaga Kerja dan Transmigrasi Provinsi Sulawesi Selatan - Nursyam Nursyam; Dita Rahmawati (Economy Deposit Journal (E-DJ), 2020)
Work motivation is important in the life of an agency or company because with optimal motivation to produce maximum performance, to encourage work motivation to create a good and healthy work environment, the Office of Manpower and Transmigration of South Sulawesi Province, Makassar City is a government agency that handles manpower issues, in general providing services to the community. So all forms of work problems or obstacles that exist must be handled more precisely so that the credibility of the South Sulawesi Provincial Manpower and Transmigration Office is maintained. This study aims to determine the effect of work motivation on employee performance at the Manpower and Transmigration Office of South Sulawesi Province. This research is causality in which the measurement of research variables is in the form of numbers and analyzes in the form of statistics. This research approach takes several stages, namely collecting data through a questionnaire or questionnaire, analyzing data, and testing hypotheses. The aim is to determine the effect of work motivation on employee performance at the Office of Manpower and Transmigration of South Sulawesi Province.The population in this study were 207 employees at the Manpower and Transmigration Office of South Sulawesi Province. Sampling using the Slovin formula with a total of 67 employees. Observation and questionnaire data collection techniques, with simple linear regression testing. work motivation variable affects the performance of the employees of the Department of Manpower and Transmigration of South Sulawesi Province. Work and Transmigration of South Sulawesi Province.